Phyllosomata associated with large gelatinous zooplankton: hitching rides and stealing bites. (3rd October 2014) - O'Rorke, Richard; Lavery, Shane D.; Wang, Miao; Gallego, Ramón; Waite, Anya M.; Beckley, Lynnath E.; Thompson, Peter A.; Jeffs, Andrew G.
Abstract: During a zooplankton survey 350 km off the coast of Western Australia, we captured a large and robust zooid of a salp ( Thetys vagina ), to which six late stage larvae (phyllosomata) of the western rock lobster ( Panulirus cygnus ) were attached. High-throughput sequencing analyses of DNA extracts from midgut glands of the larvae confirmed that each phyllosoma had consumed mainly salp tissue (x ¯ = 64.5% ± 15.9 of DNA reads). These results resolve long-standing conjecture whether spiny lobster phyllosomata attach to large gelatinous hosts to feed on them.